MDO stretched PE high-barrier film
Through the combination of MDO stretching process and specific raw materials, a PE high-barrier film with excellent barrier and mechanical properties was prepared, which solved the problem of insufficient oxygen permeability of polyethylene film, and achieved stronger gas and water vapor barrier and suppression. Bacterial effect.
Patent Information
- Application Number
- CN202411209918.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polyethylene film has poor barrier properties on oxygen, which cannot effectively prevent oxygen from passing through in the external environment, and the mechanical strength is insufficient, resulting in application restrictions in the field of packaging films.
PE high barrier film is prepared by MDO stretching process, and by using polyethylene and ethylene-vinyl alcohol copolymer and photosensitizer as the main raw materials, it is formed by extrusion, blowing film, longitudinal stretching and adhesive coating. Films with excellent barrier properties.
The oxygen and water vapor barrier properties of the film are significantly improved, the mechanical properties are enhanced, and the antibacterial effect is achieved through photodynamic reactions, solving the problem of the reduction of oxygen barrier properties of ethylene-vinyl alcohol copolymers.
Smart Images

Figure BDA0005020065630000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyethylene film preparation, and particularly relates to an MDO stretched PE high-barrier film. Background Art
[0002] MDO (Machine Direction Orientation) is the abbreviation of film machine direction stretching, that is, longitudinal stretching. Generally speaking, the MDO process is to stretch the film produced by the blown film or cast film production line at a certain temperature and stretch ratio, and then heat treat it, and then cool it to room temperature. This process can be carried out both online and offline. Using MDO technology to stretch the film can not only improve the transparency and gloss, rigidity and tear strength and barrier properties of the film, and the uniformity of the film thickness; at the same time, it can also thin the film, save raw materials, and reduce costs; and the processing is self-contained, reducing the production process.
[0003] The patent application with publication number CN109251692 A discloses a high barrier antibacterial PE film and its preparation method, wherein the high barrier antibacterial PE film is obtained by adding a nano-composite modified masterbatch to an LDPE matrix resin and extruding and blowing the high barrier antibacterial PE film; the mass of the nano-composite modified masterbatch is 3-8% of the mass of the LDPE matrix resin; the nano-composite modified masterbatch is obtained by blending and extruding an organic montmorillonite loaded with nano-ZnO, LDPE and maleic anhydride grafted polyethylene; the organic montmorillonite loaded with nano-ZnO is obtained by intercalating and compounding the montmorillonite loaded with nano-ZnO and an intercalation agent; the montmorillonite loaded with nano-ZnO is obtained by loading montmorillonite with nano-ZnO. Compared with pure PE film, the high barrier antibacterial PE film of the present invention has a 31% lower oxygen permeability, a 40% lower water vapor permeability and an antibacterial rate of 99.7%.
[0004] Most of the packaging films sold on the market are made of polyethylene as raw material. Polyethylene is a polymer made of ethylene monomers and is a typical thermoplastic. It has excellent mechanical properties, good water vapor barrier properties, high impact strength and light weight. However, polyethylene materials also have shortcomings. Polyethylene materials have poor oxygen barrier properties and cannot effectively prevent the penetration of oxygen in the external environment. Therefore, how to improve the barrier properties and mechanical strength of polyethylene films is the current research focus in the field of polyethylene film technology. Summary of the invention
[0005] The object of the present invention is to provide a MDO stretched PE high barrier film to improve the barrier properties of the polyethylene film.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] An MDO stretched PE high barrier film is prepared by the following steps:
[0008] 1) respectively extruding and melting the upper layer raw material and the lower layer raw material and extruding them from a die head, then blowing the film to form a film bubble, cooling the film, and then performing MDO longitudinal stretching to obtain an upper film and a lower film;
[0009] 2) applying an adhesive to the surface of the lower film, pressing the upper film thereon, and obtaining the MDO stretched PE high barrier film after cooling;
[0010] The upper layer raw material comprises 40 to 50 parts of polyethylene and 20 to 30 parts of barrier agent by weight;
[0011] The lower layer raw materials include 30 to 40 parts of polyethylene, 15 to 25 parts of barrier agents and 2 to 6 parts of photosensitizers by weight.
[0012] Furthermore, the barrier agent is one of ethylene-vinyl alcohol copolymer or polyamide.
[0013] Furthermore, the ethylene content of the ethylene-vinyl alcohol copolymer is 35-45%, and the vinyl alcohol content is 55-65%.
[0014] Since ethylene-vinyl alcohol copolymer contains hydroxyl groups in its molecules, it has strong hydrophilicity and hygroscopicity. After ethylene-vinyl alcohol copolymer absorbs moisture, its barrier properties will decrease. By increasing the ethylene content in ethylene-vinyl alcohol copolymer, the corresponding hydroxyl content will decrease, the hydrophilicity will decrease, the barrier to water molecules will increase, and the processability will improve, but the barrier to oxygen will decrease.
[0015] Furthermore, the photosensitizer is one of tetrakis(4-carboxyphenyl)porphine, porphyrin sodium or dihydrochlorin e6.
[0016] Furthermore, the adhesive is a water-based polyurethane adhesive.
[0017] Furthermore, during the extrusion melting, the temperature of the screw is 175-180°C, and the temperature of the die is 180-185°C.
[0018] Furthermore, the heating temperature of the MDO longitudinal stretching is 105-110° C., and the stretching ratio is (2-3):1.
[0019] Furthermore, the adhesive coating temperature is 110-115° C., the pressing temperature is 85-90° C., and the cooling time is 1 to 1.5 hours.
[0020] Beneficial effects of the present invention:
[0021] (1) The ethylene-vinyl alcohol copolymer used in the present invention has excellent barrier properties and is non-toxic and environmentally friendly, and can prevent gases such as oxygen from penetrating from the outside; in addition, the ethylene-vinyl alcohol copolymer and polyethylene have similar structures, and the compatibility between the materials is good, which enhances the mechanical properties after film formation.
[0022] (2) The photosensitizer molecules used in the present invention can convert ground state molecular oxygen into singlet oxygen after absorbing photon energy, and singlet oxygen can oxidize biologically active macromolecules, induce oxidative stress response in target tissues, and induce cell death, thereby achieving an antibacterial effect; in addition, a hydroxyl-containing porphyrin photosensitizer is used to form hydrogen bonds with the hydroxyl groups in the ethylene-vinyl alcohol copolymer, thereby enhancing the binding force between the materials; at the same time, the photosensitizer molecules are located in the lower layer of the barrier film, and even under light, they avoid reacting with external oxygen; by photodynamically reacting with oxygen molecules that are not successfully blocked, the problem of decreased oxygen barrier properties of the ethylene-vinyl alcohol copolymer molecules is also solved.
[0023] (3) The MDO process adopted in the present invention stretches the film, thereby improving the transparency, uniformity, mechanical strength and barrier properties of the film; at the same time, the film can be thinned, saving raw materials and reducing production processes. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1
[0026] This embodiment provides a MDO stretched PE high barrier film, which is prepared by the following steps:
[0027] 1) 40 parts of polyethylene and 20 parts of ethylene-vinyl alcohol copolymer (45% ethylene and 55% vinyl alcohol) are uniformly mixed to obtain an upper layer mixture, and 30 parts of polyethylene, 15 parts of ethylene-vinyl alcohol copolymer (45% ethylene and 55% vinyl alcohol) and 4 parts of tetrakis(4-carboxyphenyl)porphine are uniformly mixed to obtain a lower layer mixture, and the mixtures are respectively extruded and melted and then extruded from a die head, wherein the temperature of the screw during the extrusion and melting is 175° C. and the temperature of the die head is 185° C., and then film bubbles are formed by blowing and then cooled, and MDO longitudinal stretching is performed at a temperature of 105-110° C., and the stretch ratio is 2:1 to obtain an upper film and a lower film.
[0028] 2) A water-based polyurethane adhesive was coated on the surface of the lower film at 115° C. After the temperature dropped to 85° C., an upper film was pressed thereon, and after cooling for 1.5 hours, an MDO-stretched PE high-barrier film was obtained.
[0029] Example 2
[0030] Compared with Example 1, this embodiment differs in that the composition of the upper and lower mixed materials in step 1) is changed, and the specific implementation steps are as follows:
[0031] 1) 50 parts of polyethylene and 30 parts of ethylene-vinyl alcohol copolymer are uniformly mixed to obtain an upper layer mixture, 30 parts of polyethylene, 25 parts of a barrier agent and 4 parts of tetrakis(4-carboxyphenyl)porphine are uniformly mixed to obtain a lower layer mixture, the mixtures are respectively extruded and melted and then extruded from a die head, wherein the temperature of the screw during the extrusion and melting is 175° C. and the temperature of the die head is 185° C., then a film is blown to form a film bubble and then cooled, and MDO longitudinal stretching is performed at a temperature of 105-110° C., and the stretching ratio is 2:1 to obtain an upper film and a lower film.
[0032] The remaining raw materials and preparation process remain the same as in Example 1.
[0033] Example 3
[0034] The difference between this embodiment and embodiment 1 is that "ethylene-vinyl alcohol copolymer" is replaced by "polyamide".
[0035] The remaining raw materials and preparation process remain the same as in Example 1.
[0036] Example 4
[0037] The present embodiment is different from the embodiment 1 in that the “ethylene-vinyl alcohol copolymer (45% ethylene and 55% vinyl alcohol)” is replaced with the “ethylene-vinyl alcohol copolymer (35% ethylene and 65% vinyl alcohol)”.
[0038] The remaining raw materials and preparation process remain the same as in Example 1.
[0039] Example 5
[0040] The present embodiment is different from the embodiment 1 in that "tetrakis(4-carboxyphenyl)porphine" is replaced with "dihydrochlorin e6".
[0041] The remaining raw materials and preparation process remain the same as in Example 1.
[0042] Example 6
[0043] The present embodiment is different from the embodiment 1 in that the stretching ratio in step 1) is changed to a stretching ratio of 3:1.
[0044] The remaining raw materials and preparation process remain the same as in Example 1.
[0045] Comparative Example 1
[0046] The difference between this comparative example and Example 1 is that no ethylene-vinyl alcohol copolymer is added.
[0047] The remaining raw materials and preparation process remain the same as in Example 1.
[0048] Comparative Example 2
[0049] The difference between this comparative example and Example 1 is that tetrakis(4-carboxyphenyl)porphine is not added.
[0050] The remaining raw materials and preparation process remain the same as in Example 1.
[0051] Comparative Example 3
[0052] Compared with Example 1, the difference between this comparative example is that the MDO stretching process is not used in step 1), and the specific implementation steps are as follows:
[0053] 1) 40 parts of polyethylene and 20 parts of ethylene-vinyl alcohol copolymer are uniformly mixed to obtain an upper layer mixture, and 30 parts of polyethylene, 15 parts of ethylene-vinyl alcohol copolymer and 4 parts of tetrakis(4-carboxyphenyl)porphine are uniformly mixed to obtain a lower layer mixture, and the mixtures are respectively extruded and melted and then extruded from a die head, wherein the temperature of the screw during the extrusion and melting is 175° C. and the temperature of the die head is 185° C., and then the film is blown and plasticized and then cooled to obtain an upper film and a lower film.
[0054] The remaining raw materials and preparation process remain the same as in Example 1.
[0055] Comparative Example 4
[0056] This comparative example is different from Example 1 in that ethylene-vinyl alcohol copolymer and tetrakis(4-carboxyphenyl)porphine are not added, and the specific implementation steps are as follows:
[0057] 1) 40 parts of polyethylene are used as the upper layer material, and 30 parts of polyethylene are used as the lower layer material, which are extruded and melted respectively and then extruded from a die head, wherein the temperature of the screw during the extrusion and melting is 175° C., and the temperature of the die head is 185° C., and then the film is blown to form a bubble and then cooled, and MDO longitudinal stretching is performed at a temperature of 105-110° C., and the stretching ratio is 2:1 to obtain an upper film and a lower film.
[0058] 2) A water-based polyurethane adhesive was coated on the surface of the lower film at 115° C. After the temperature dropped to 85° C., an upper film was pressed thereon, and after cooling for 1.5 hours, an MDO-stretched PE high-barrier film was obtained.
[0059] The remaining raw materials and preparation process remain the same as in Example 1.
[0060] Comparative Example 5
[0061] The difference between this comparative example and Example 1 is that no light treatment is performed in the subsequent test.
[0062] The remaining raw materials and preparation process remain the same as in Example 1.
[0063] Performance tests were performed on Examples 1 to 6 and Comparative Examples 1 to 5, wherein Comparative Example 5 was not subjected to light treatment;
[0064] According to GB / T 1038-2022 “Test Method for Gas Permeability of Plastic Films and Sheets”, the barrier films obtained in various embodiments and comparative examples of the present application were tested for oxygen permeability under ordinary light for 20 minutes;
[0065] According to GB / T 1037-2021 "Determination of water vapor permeability of plastic films and sheets", the barrier films obtained in each embodiment and comparative example of the present application were tested for water vapor permeability;
[0066] According to GB / T 1447-2005 "Test Method for Tensile Properties of Fiber Reinforced Plastics", the protective films obtained in various embodiments and comparative examples of the present application were tested for tensile properties;
[0067] According to GB / T 31402-2023 "Determination of antibacterial activity on the surface of plastics and other non-porous materials", after the barrier film is in contact with bacteria, it is exposed to ordinary light for 20 minutes, and the antibacterial rate of the barrier film obtained in each embodiment and comparative example of the present application is tested;
[0068] The results are shown in Table 1:
[0069] Table 1
[0070]
[0071] As can be seen from Table 1, compared with Example 1, Example 3 shows a decrease in mechanical properties. This is because the compatibility of polyamide with the material is not as good as that of ethylene-vinyl alcohol copolymer, which affects the mechanical properties of the barrier film; compared with Example 1, Example 4 is more hydrophilic due to the increase in the proportion of vinyl alcohol, and the barrier property to water vapor is reduced; compared with Example 1, due to the presence of carboxyl groups in tetrakis(4-carboxyphenyl)porphine, tetrakis(4-carboxyphenyl)porphine has better compatibility than dihydrochlorin e6; compared with Example 1, Example 6 has a lower tensile strength of the film due to the excessive stretching ratio of the MDO stretching process.
[0072] Compared with Example 1, the results of Comparative Example 1 show a significant decrease in the barrier properties of the film, because ethylene-vinyl alcohol copolymer is highly crystalline and can effectively prevent the penetration of oxygen and water vapor; compared with Example 1, the antibacterial properties of the barrier film of Comparative Example 2 are significantly reduced after no photosensitizer is added, because in the process of generating active oxygen by photodynamic reaction, light source, oxygen and photosensitizer are indispensable; compared with Example 1, the mechanical properties and barrier properties of the final barrier film of Example 3 show a downward trend, because the film after stretching forms smaller crystals and the molecular chain segments are in the MD direction, which makes the crystallinity in the MD direction higher, thereby improving the barrier properties and mechanical properties of the film; compared with Example 1, in Comparative Example 5, the photodynamic reaction cannot be carried out without light treatment, resulting in poor antibacterial effect.
[0073] In summary, the MDO stretched PE high barrier film provided by the present invention has good oxygen and water vapor barrier properties, strong mechanical properties and good antibacterial properties, and has good application prospects in the field of polyethylene film preparation technology.
[0074] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0075] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A MDO stretched PE high barrier film, characterized in that: Prepared by the following steps: 1) The upper layer raw material and the lower layer raw material are respectively extruded and melted and then extruded from a die head, and then blown into a film bubble and then cooled, and then longitudinally stretched by MDO to obtain an upper film and a lower film; 2) applying an adhesive to the surface of the lower film, pressing the upper film thereon, and obtaining the MDO stretched PE high barrier film after cooling; The upper layer raw material comprises 40 to 50 parts of polyethylene and 20 to 30 parts of barrier agent by weight; The lower layer raw materials include 30 to 40 parts of polyethylene, 15 to 25 parts of barrier agents and 2 to 6 parts of photosensitizers by weight.
2. The MDO stretched PE high barrier film according to claim 1, characterized in that: The barrier agent is one of ethylene-vinyl alcohol copolymer or polyamide.
3. The MDO stretched PE high barrier film according to claim 2, characterized in that: The ethylene content of the ethylene-vinyl alcohol copolymer is 35-45%, and the vinyl alcohol content is 55-65%.
4. The MDO stretched PE high barrier film according to claim 1, characterized in that: The photosensitizer is one of tetrakis(4-carboxyphenyl)porphine, porphin sodium or dihydrochlorin e6.
5. The MDO stretched PE high barrier film according to claim 1, characterized in that: The adhesive is a water-based polyurethane adhesive.
6. The MDO stretched PE high barrier film according to claim 1, characterized in that: The temperature of the screw during the extrusion melting is 175-180°C, and the temperature of the die head is 180-185°C.
7. The MDO stretched PE high barrier film according to claim 1, characterized in that: The heating temperature of the MDO longitudinal stretching is 105-110° C., and the stretching ratio is (2-3):
1.
8. The MDO stretched PE high barrier film according to claim 1, characterized in that: The adhesive coating temperature is 110-115° C., the pressing temperature is 85-90° C., and the cooling time is 1 to 1.5 hours.
Citation Information
Patent Citations
Anti-degumming PE protective film, and preparation method thereof
CN109251692A
High-resistance co-mixing material with multilayer structure
CN105131483A
Multi-layer co-extrusion film-blowing online longitudinal stretching high-barrier thin film and preparation method thereof
CN109591415A
Antibacterial polymer coating composition and antibacterial polymer film
CN112585227A
High-barrier film and production method thereof
CN114407460A